Non-invasive assessment and prediction of clinically significant portal hypertension. (13th March 2011) - Rye, K; Mortimore, G; Austin, A; Freeman, J
Abstract : Introduction: Hepatic venous pressure gradient (HVPG) predicts variceal development, bleeding, clinical decompensation and death. Measurement is invasive, time-consuming and performed in few centres. Reduction of HVPG to ≥12 mm Hg or by >20% significantly reduces bleeding risk and mortality. Detection of non-responders requires repeated HVPG measurement as conventional non-invasive assessment is not accurate in predicting haemodynamic response. Cirrhotics have a hyperdynamic circulation and impaired baroreceptor sensitivity (BRS). The authors assessed whether non-invasive measurement of systemic haemodynamics and BRS detected clinically significant portal hypertension (CSPH, HVPG ≥12 mm Hg). Methods: Prospective study of 29 cirrhotic patients. Systemic haemodynamics were assessed non-invasively using the Finometer. Spontaneous BRS was calculated from the regression of pulse interval on systolic blood pressure. Portal pressure was assessed by measurement of HVPG in 27 patients. Results: 69% male, median age 47 (42–55) years, CPS 6 (Class A 18, B 10, C 1) and MELD 10 (8–13). HVPG significantly correlated with CI, HR, BRS, Child-Pugh score, MELD, prothrombin time, albumin and bilirubin. Differences in these parameters according to HVPG and comparison of AUROC curves to predict CSPH are summarised in the table 1 . At a cut-off of 71.75 bpm, HR predicted CSPH with 100% sensitivity, 86% specificity, 95% PPV, 100% NPV and correctly classified 96% of patients. A HR of 75.93 bpm gave 100% specificity and PPV. At a cut-off of 3.78 l/min/m 2, CI predicted CSPH with 55% sensitivity, 100% specificity and 100% PPV. At a cut-off of 4.86 ms/mm Hg BRS predicted CSPH with 70% sensitivity, 100% specificity and PPV. Conclusion: Significant differences in CI, HR and BRS, assessed non-invasively, are seen in cirrhotic patients with CSPH. While optimal cut-offs for prediction remain to be defined it may be possible to non-invasively diagnose or exclude CSPH. It also opens up future potential for non-invasive monitoring of responses to therapeutic intervention.